Velocity correlated crack front and surface marks in single crystalline silicon - Lv Zhao (Nature Portfolio, 2018)
Single crystal silicon cracking, a problem in solar cell operation, remains difficult to accurately predict. Here, the authors show that a silicon single crystal surprisingly cleaves without crack deviation, and that the crack front is accompanied by special marks due to local velocity changes.